The Effects Of Graphics And Animation With Worked Examples In The Teaching Of Electrolysis On Learners With Different Cognitive Styles - Low, Boon Peng (2013)
This study investigated the impact of worked example effect and animated graphic effect in worked example in multimedia learning courseware towards learners‟ achievement for learners with different cognitive styles.Three different presentation modes of multimedia learning courseware, namely (i) Example with Static Graphic mode (ESG), (ii) Worked Example with Static Graphic mode (WESG) and (iii) Worked Example with Animated Graphic mode (WEAG), were systematically designed and developed to serve the purpose of this study. This quasi-experimental study employed a 3 x 2 factorial design by taking the three different presentation modes of multimedia learning courseware (ESG, WESG and WEAG) as the independent variable and the learners‟ cognitive styles of field-dependence/field-independence (FD/FI) as the moderator variable. The dependent variable was the learners‟ achievement score. Descriptive and inferential statistics were performed to analyse the data. The analyses revealed that learners who learned with WESG mode performed significantly better compared to those who learned with ESG mode. When the learners‟ cognitive styles were taken into consideration, the FD learners who learned with WESG mode performed significantly better compared to FD learners who learned with ESG mode. Among FI learners, the FI learners who learned with WESG mode performed significantly better compared to FI learners who learned with ESG mode. When taking the learners as whole, the analyses also revealed that learners who learned with WEAG mode does not performed significantly better compared to those who learned with WESG mode.